Rumah Komik Di Pekanbaru Berdasarkan Prinsip Desain Tadao Ando (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Comic is a visualization of life and one thing that is not foreign anymore, even with the advances in technology that rapidly at this time, the comic can be found easily. So, comics are part of the creative industries which are able to reap much profit in the sales. But the kind of comic that sold well in the market is kind of foreign comics such as manga (Japans comic), while the local comic less attractive to readers. For that needed a place to improve the quality of Indonesias comic and comic in order to be accepted by the society. To achieve these goals the Comic House provides a variety of facilities that hosts a variety of activities in the field of education, production, promotion and recreation. Comic House was designed using design principles of Tadao Ando. Tadao Ando using Zen philosophies and Traditional architecture of Japan in his design to produce a concept of provocation through exploration of the space he created. These principles apply to the wholeelement of design, starting from order of exterior, building forms, until the Comic House interior. Users are invited to take a walking tour and experience the space from the entrance to the exit in accordance with the functions of the comics as a media provocation that is inviting readers to feel the meaning of a story. With an approach based on the design principles of Tadao Ando, then mass produced with a geometry such as a rectangle (the simplicity of the form), the order of mass mutualsustainability, exterior and interior that reflects the Zen philosophy and Traditional Architecture of Japan as well as the facade without ornament. The Comic House design also pay attention to the aspect of a tropical climate so that there is an adjustment against the design principles of Tadao Ando.Key words : Comic, Comic House, Provocation, and The Design Principles of Tadao Ando